SINGING ETHOS, PATHOS, AND ETHNOS: THREE GENERATIONS, FOUR ISRAELI EUROVISION VICTORIES, 1978–2018 / ПЕСНИ ЭТОСА, ПАФОСА И ЭТНОСА: ТРИ ПОКОЛЕНИЯ — ЧЕТЫРЕ ПОБЕДЫ ИЗРАИЛЯ НА «ЕВРОВИДЕНИИ» (1978–2018) - RITZAREV MARINA / РЫЦАРЕВА МАРИНА ГРИГОРЬЕВНА (Наука телевидения)
The article analyzes the musical and extra-musical factors that may have influenced Israeli victories in the Eurovision Song Contest in 1978, 1979, 1998, and 2018. The role of folklore elements, sociohistorical and geopolitical contexts are considered. The victory of the song-show “Toy” (Netta Barzilai, 2018) is viewed as result of a complex strategy, constructing a self-sufficient antimodel image and exploiting different factors like devotion of queer community to the Eurovision and public solidarity with victims of sexual assault #MeToo. The case of Dana International (1998) is viewed against the background of the LGBT movement culminating in the late 1990s in its struggle for acquiring recognition as sociopolitical power and resulting in support by the European Union. The article focuses on two Israeli songs winning in 1978 and 1979: “Abanibi” (music: Nurit Hirsh; lyrics: Ehud Manor; soloist Izhar Cohen) and “Halleluyah” (music: Kobi Oshrat; lyrics: Shitrit Or; soloist Gali Atari). They are considered through paradigm of folklore elements and national cultural symbols. The author uses her theory of vernacularity in music subdividing it into phylo-vernacular and onto-vernacular types/functions. The former applies mainly to the primordial folklore associated with ritualistic agricultural societies, and characterized by stability; the latter applies to the folklore practiced by an urbanized population and implies an ongoing process of interaction between the initial corpus and popular music, openness to influences and borrowings, and a separation from ritual. The onto-vernacular is characterized by changeability. The Eurovision presents a global culture “locus,” an extreme meeting point between the two types of vernacular. Phylo-vernacular elements, ingrained in each country’s cultural roots, are here mixed with a general, global pop style creating onto-vernacular, aimed at intercultural communication aesthetic preferences. Use of both types/functions reflects national identity of participating countries.